Experience with newborn hearing screening in a tertiary hospital: a 6-month review from Kaniyakumari - D., Jude Anselm Shyras; S., Ganapathy; C., Subramonia Biju; R., Suneer; Raj, Mathan; R., Kiruthiga; A., Anagha (International Journal Of Community Medicine And Public Health, 2024)
Background: Early identification of congenital hearing loss is vital for optimal language, cognitive, and social development. Despite its significance, universal newborn hearing screening (UNHS) programs are not well-established in many regions of India. This study aimed to determine the prevalence of congenital hearing loss and assess the performance of otoacoustic emissions (OAE) and brainstem evoked response audiometry (BERA) in a tertiary care setting in Kanyakumari. Methods: A retrospective review was performed on 830 newborns delivered at Kanyakumari Government Medical College Hospital from July to December 2022. All newborns underwent initial OAE screening within 24 to 72 hours of birth or prior to neonatal intensive care unit (NICU) discharge. Infants failing the second OAE screening were further evaluated with BERA. Relevant risk factors were documented, and families received counselling regarding follow-up. Results: The incidence of congenital hearing loss was found to be 0.12%. Of the 93 infants who required repeat screening after failing the first OAE, 21 failed the second test, and one was confirmed to have hearing loss through BERA. The first OAE had a sensitivity of 100% and a specificity of 89%, while the second OAE maintained 100% sensitivity and 78% specificity. Family history of hearing impairment was a significant risk factor (p<0.001). Conclusions: This study highlights the practicality and efficacy of implementing UNHS in resource-constrained areas. OAE proves to be a reliable initial screening method, with BERA serving as a robust confirmatory tool. Improved awareness and access to healthcare can further enhance program success.